اخلاقيات العمل في المؤسسات الاقتصادية - سكينة, بسرة; هندة, بوطي; امينة, بن حمزة; انفال, مدني (جامعة الوادي - University of Eloued, 2023)
تهدف الدراسة إلى تحديد مستوى الإلتزام بأخلاقيات العمل في مؤسسة اتصالات الجزائر بالوادي، وذلك من خلال التركيز على البعد القانوني، البعد الإنساني، البعد الثقافي والبعد الوظيفي، وقد تم استخدام المنهج الوصفي لوصف وتحليل متغيرات الدراسة وأبعادها المختلفة، وأيضا تم الاعتماد على استمارة الاستبيان كأداة في جمع المعلومات والبيانات، حيث وزعت 30 استمارة وكان منها 28 استمارة صالحة للتحليل، وبناء على تحليل المعطيات والمعلومات، توصلت الدراسة إلى العديد من النتائج، من أهمها أن درجة الإلتزام بالأطر القانونية والالتزام الوظيفي كانت جيدة في مؤسسة اتصالات الجزائر بالوادي، بينما جاء مستوى الاهتمام بالجانب الإنساني وأيضا بالبعد الثقافي مقبول في مؤسسة اتصالات الجزائر بالوادي. The study aims to determine the level of commitment to work ethics in the Algeria Telecom Corporation in the Valley, by focusing on the legal dimension, the human dimension, the cultural dimension and the functional dimension. The descriptive approach was used to describe and analyze the variables of the study and its various dimensions. Collecting information and data, where 30 questionnaires were distributed and 28 of them were valid for analysis, and based on the analysis of data and information, the study reached many results, the most important of which is that the degree of commitment to legal frameworks and functional commitment was good in Algeria Telecom Corporation in the Valley, while the level of interest in the aspect came The human as well as the cultural dimension is accepted in Algeria Telecom in El Oued.
Keywords: أخلاقيات العمل، البعد القانوني، البعد الإنساني، البعد الثقافي، البعد الوظيفي، مؤسسة اتصالات الجزائر.; work ethics, legal dimension, human dimension, cultural dimension, functional dimension, Algeria Telecom Corporation.